1998
DOI: 10.1055/s-2007-978942
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccination with Glutamic Acid Decarboxylase (GAD) Generates a Strong Humoral Immune Response in BALB/c, C57BL/6, and in Diabetes-Prone NOD Mice

Abstract: The technique of DNA-based vaccination was used to generate a T-cell-dependent antibody response to glutamic acid decarboxylase (GAD) in BALB/c, C57BL/6, and non-obese diabetic (NOD) mice. Plasmids were constructed in which the expression of the rat GAD65 (rGAD65) or the rat GAD67 (rGAD67) gene was driven by the immediate early region promoter of the human cytomegalovirus (pCMV). This "naked" plasmid DNA was then injected into the regenerating muscles of the studied mice. In the vaccinated animals, antibody re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Several investigators have reported protection against autoimmune diabetes by DNA vaccination against isletcell antigens (insulin, GAD65 or other) in NOD mice or other diabetes models (Table 3). [50][51][52][53][54][55][56][57][58][59][60][61] In the vast majority of cases, DNA was delivered i.m. without electroporation.…”
Section: Dna Vaccination Against T1dmentioning
confidence: 99%
“…Several investigators have reported protection against autoimmune diabetes by DNA vaccination against isletcell antigens (insulin, GAD65 or other) in NOD mice or other diabetes models (Table 3). [50][51][52][53][54][55][56][57][58][59][60][61] In the vast majority of cases, DNA was delivered i.m. without electroporation.…”
Section: Dna Vaccination Against T1dmentioning
confidence: 99%
“…Other studies have investigated effects of GAD‐DNA vaccination in NOD mice which develop a high diabetes incidence [17,18,20,22,31]. In another study [30], a single immunization of 6‐week‐old mice with GAD plasmid provided a low diabetes enhancement during the first stage after DNA vaccination but was not durable, possibly because of the lack of a second DNA injection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with our study and those of Wiest Ladenburger et al . [30] and Balasa et al . [17], other studies [20,31] did not include pretreatment with cardiotoxin, which leads to muscle regeneration and improves DNA immunization efficiency [33].…”
Section: Discussionmentioning
confidence: 99%
“…injection of plasmid DNA encoding different forms of GAD to prevent diabetes in NOD mice. In many cases, delivery of a cDNA coding for intracellular GAD65 not only does not appear to be effective (Wiest-Ladenburger et al, 1998;Filippova et al, 2001), but can even be pro-inflammatory (Bot et al, 2001;Tisch et al, 2001;Wolfe et al, 2002). In contrast, injection of DNA coding for a secreted polypeptide derived from GAD65 is more likely to suppress the disease, although the effects are dependent on DNA dosage or codelivery of a cytokine (Filip-…”
Section: Discussionmentioning
confidence: 99%